Personal computer base tap changer / Abdul Razak Ruslan - Ruslan, Abdul Razak (1998)
This project describe the development of PC Base Tap Changer by using computer controlled. Tap Changer one of the most economical controlled switch that will change tap connection as required to maintain a constant output voltage.